Проявление сверхпроводящих флуктуаций в характеристиках андреевских контактов Bi2223-Ag при Т > Tс - Сидоров, С.Л.; Дьяченко, А.И.; Таренков, В.Ю.; Заводовский, В.Ф. (Физика и техника высоких давлений, 2013)
Проведены спектроскопические исследования андреевских контактов для высокотемпературного сверхпроводника Bi2223 с критической температурой Тс = 110 K. Контакты NS-типа Bi2223−Ag демонстрировали энергетическую щель Δ в районе V = 50 mV. Обнаружено существование избыточного тока Iexc в широком температурном интервале T > Tc. Наличие избыточного тока в этом температурном интервале означает присутствие некогерентных куперовских пар с энергией связи соответствующей псевдощели, которая наблюдается в спектрах фотоэмиссии. Проведено спектроскопічні дослідження андріївських контактів для високотемпературного надпровідника Bi2223 з критичною температурою Тс = 110 K. Контакти NS-типу Bi2223−Ag демонстрували енергетичну щілину Δ в районі V = 50 mV. Виявлено існування надлишкового струму Iexc в широкому температурному інтервалі T > Tс. Наявність надлишкового струму в цьому температурному інтервалі означає присутність некогерентних куперовських пар з енергією зв’язку відповідної псевдощілини, яка спостерігається у спектрах фотоемісії. The most problematic issue of the physics of high-temperature superconductivity is the nature of the pseudogap ΔPG in electron spectrum of cuprates. In Brillouin zone, the pseudogap ΔPG(k) is localized in the neighborhood of the points k = (0, ±π/a0), (±π/a0, 0) where a0 is the lattice constant in the CuO2 plane. Within the same area, the energy gap of Cooper pairs Δ(k) achieves the maximum. As a result, intrinsic bond can appear between two order parameters. The bond does not reduce to competition for the same areas of the Fermi surface. The solution of this problem requires experiments that are sensitive to the phase of the order parameter of a superconductor. One of these methods is Andreev reflection in normal metal−superconductor contacts, being immediately determined by the existence of Cooper pairs. At Andreev reflection, an electron injected from metal N to superconductor S forms Cooper pair in the neighborhood of NS boundary. The pair goes to condensate and a hole is reflected to the normal metal. Counter-flow of holes results in increase in the current through the contact in comparison to the current in the normal state (excess current). A singularity of conductivity of the contact dI/dV at V ≈ Δ(T)/e allows estimation of the value and the symmetry of the energy gap Δ(k). It is demonstrated in the present paper that excess conductivity and current are observed in Andreev contacts Bi1.6Pb0.4Sr1.8Ca2.2Cu3O−Ag (Bi2223−Ag) at the temperatures T < Tpair where Tpair is above Tυ ~ 140−150 K (that is the temperature of Nernst effect appearance) and substantially exceeds the temperature of superconducting transition Tc ≈ 110 K. This result agrees with detection of diamagnetic response and Nernst effect and does not contradict to recent results of photoemission spectroscopy with high angle resolution (ARPES) for Bi2223 cuprate.